English mediopassive constructions: a cognitive, corpus-based study of their origin, spread, and current status - Hundt, Marianne (Rodopi, 2010)
List of tables and figures; Preface; Chapter 1. Introduction; Chapter 2. Defining the object of study; Chapter 3. Previous studies; Chapter 4. Theoretical background; Chapter 5. The mediopassive in Present Day English; Chapter 6. The history of mediopassives; Chapter 7. Conclusion; References; Appendix 1. Primary material; Appendix 2. Sample pages of Sears & Roebucks catalogues; Appendix 3. Additional tables and figures; Index.
Includes bibliographical references (p. [181]-193) and index. - Description based on print version record
Description based on print version record
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002
Keywords: Englisch; Electronic books; Mediopassiv